PANDANGAN MULTINATIONAL CORPORATIONS(MNC) TERHADAP KASUS PENUTUPAN TIK TOKSHOP - Nuh Krama Hadianto; Herman; Dedeh Imam Fatmasari (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
In the international political economy, Multinational Corporations (MNC)have an important role in international transactions. MNCs are growingrapidly, not only from developed countries, MNCs from developingcountries too, are currently growing rapidly. The existence of MNCs canhave a big influence in global politics, so that with economic influence this can be a source for establishing relationships with society and being able tolobby politically. Currently, many multinational companies in variouscountries have very large revenues, which can even exceed the income of acountry. Like the tik tok company, but in practice this Indonesian tik tokcompany stands on a dual platform which has been officially prohibited bythe Indonesian government since 25 September 2020. The prohibition iscontained in the Revised Minister of Trade Regulation number 50 of 2020concerning Provisions for Business Licensing, Advertising, Developmentand Supervision of Business Actors in trade. Through this electronic system,one of the aims is to harmonize the offline sales of goods by traders inmarkets and other offline shops.